Cheerleader injuries: a Brazilian cross-sectional study - Isabela Bianchini Marolde; Cristiano Carvalho; Paula Regina Mendes da Silva Serrão (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to characterize the types, frequency, body locations, and activities related to cheerleading injuries. Methods: This was an Internet-based survey among Brazilian cheerleaders at the competitive national level. Data collected from participants included information about previous injuries (number, location, anatomical structure), age, sex, height, weight, occupation, cheerleading position, number of years of experience, and frequency and hours of training per week. The significance level was set at α = 0.05. Results: In total, 113 cheerleaders answered the online questionnaire, and 230 injuries were reported. The most affected anatomical site was the wrist with 14.8% of the injuries, followed by the ankle (11.3%), and the hand and fingers (9.1%). There is a direct association between the occurrence of injuries and experience cheerleading practice (p = 0.002). Conclusions: There is a considerable number of injuries in cheerleading, mostly occurring in the upper limbs. Specific preventative education or training could be directed at these athletes, with an emphasis on reducing upper limb injuries.